Psychological characteristics of parents and emotional well-being of preschool children - E.V. Ivanova; I.V. Shapovalenko (Психолого-педагогические исследования, 2025)
The work is aimed at studying the emotional well-being (EWВ) of preschool children in the context of the social situation of development and in connection with such characteristics of parents as their level of resilience, implemented types of upbringing of children and individually specific protective models in the situation of marital conflicts. The hypothesis of the study: the EWВ of preschool children is associated with the resilience of their parents. Parents (mothers and fathers) with a high level of resilience are able to create a more favorable context for the development of children, build more effective and harmonious marital and parent-child relationships, which ensures a high level of EWВ in preschool children. A number of empirical hypotheses have been formulated: 1. A high level of EW in preschool children is associated with a high level of resilience of parents (mothers, fathers). 2. A high level of EWВ in preschool children is associated with the use of less disturbed types of upbringing by parents (mothers and fathers). 3. High level of EBВ in preschool children is associated with moderate use of individually specific protective models by parents in situations of marital conflicts. The study involved complete families with normotypic preschool children and teachers of preschool institutions in Moscow (N=441). The sample includes: a group of children (N=141) aged 5 to 7 years (M=6,12, SD=0,66), including 90 boys and 51 girls; a group of their parents (N=282) aged 30 to 34 years (M=32,67, SD=1,55), including 141 fathers and 141 mothers; a group of preschool teachers (N=18) aged 38 to 40 years (M=39,55, SD=0,85), all female respondents. The methods used: questionnaire for parents "Psychological anamnesis" (G.V. Burmenskaya, in our modification), questionnaire for teachers "Expert assessment sheet" (according to L. Stott, in our modification), anxiety test "Choose the right face" (R. Tamml et al.), test "Ladder" (modified by A.M. Prikhozhan), projective test "Family drawing" (modified by A.L. Venger); questionnaire "Analysis of family relationships" (AFR) (authors E.G. Eidemiller, V.V. Yustitskis), questionnaire "Reactions of spouses to conflict" (authors A.S. Kocharyan, G.S. Kocharyan, A.V. Kirichuk), resilience test (S. Maddi, in the adaptation of D.A. Leontiev, E.I. Rasskazova). A factor analysis was conducted using the principal component method based on the indicators of 5 methods for assessing the EWB of preschool children (N=141) and the general level of EWB of preschool children; EWB factors were identified for children with different levels of EWB. The method of correlation analysis revealed that the EWB of preschool children is significantly directly related to the resilience of fathers, and significantly inversely related to the use of types of disrupted upbringing by parents, with the intensity of individually specific protective models in mothers and fathers in a situation of marital conflicts.